2014
DOI: 10.5114/jcb.2014.45031
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant vaginal cuff brachytherapy for high-risk, early stage endometrial cancer

Abstract: PurposeTo report outcomes following adjuvant high-dose-rate vaginal brachytherapy (VBT) with or without chemotherapy for high-intermediate risk (HIR) and high-risk, early stage endometrial cancer as defined in Gynecologic Oncology Group trial 0249.Material and methodsFrom May 2000 to January 2014, 68 women with HIR and high-risk endometrial cancer underwent surgical staging followed by VBT. Median VBT dose was 21 Gy delivered in three fractions prescribed to 0.5 cm depth. Paclitaxel 175 mg/m2 and carboplatin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Table 4 describes the outcomes of VBT with or without CT for patients with high risk histologies. Vaginal failure is generally low (range of 0–2.7%) though pelvic failure ranges from 0–9.0% for patients with stage I–II disease [33,5559]. …”
Section: Vaginal Brachytherapymentioning
confidence: 99%
“…Table 4 describes the outcomes of VBT with or without CT for patients with high risk histologies. Vaginal failure is generally low (range of 0–2.7%) though pelvic failure ranges from 0–9.0% for patients with stage I–II disease [33,5559]. …”
Section: Vaginal Brachytherapymentioning
confidence: 99%
“…27,28 It is interesting to note that over time the application of chemotherapy in endometrial cancer has been adopted by clinicians in patients with high-risk endometrial cancer as shown in a recently published questionnaire among members of the Society of Gynecologic Oncologists and supported by data that VBT alone is not sufficient in patients with high-risk EC. 29,30 Although our data support the consideration of adjuvant chemotherapy in high-risk endometrial cancer patients, data should be confirmed by randomized trials. Especially, because early data of the GOG 249 study, that randomized high-intermediate-, and high-risk patients between pelvic EBRT and vaginal brachytherapy followed by chemotherapy (3 cycles of carboplatin and paclitaxel) did not show a benefit with respect to PFS of adjuvant chemotherapy over standard EBRT.…”
Section: Discussionmentioning
confidence: 63%
“…Chadha .1%, respectively. The 3-yr disease-free and overall survival rates were 87.7% and 93.9%, respectively [15].…”
Section: Discussionmentioning
confidence: 97%